The effect of 4 weeks chair-based exercise on cognitive function in the elderly - Roy Mal; Mariani Santosa; Nawanto Agung Prastowo; Nelson Sudiyono; Ignatio Rika Haryono (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Degenerative processes in the central nervous system contribute to in cognitive function decline in the elderly. Physical exercise may prevent this decline. However, elderly people often require modified forms of activity to ensure both safety and effectiveness. This study aimed to investigate the the effect of chair-based exercise (CBE) on cognitive function in elderly people. This study was conducted a two nursing homes using a two-group pretest and posttest experimental design with a control group. All participants were informed about the procedures of study, provided written informed consent, and underwent an initial cognitive assessment using the mini-mental state examination (MMSE). Participants in the intervention group engaged in CBE sessions over a four-week period. Following the intervention, cognitive function was reassessed in both groups. The Wilcoxon signed-rank test was used to analyze within-group changes, while independent t-tests were used to assess between-group differences in cognitive function scores. A significant improvement in cognitive function was observed in the intervention group after the four-week CBE program (p = 0.008). Moreover, a significant between-group difference in cognitive score changes was found (p = 0.003), favoring the intervention group. In conclusion, a four-week CBE program significantly improved cognitive function among elderly participants. These findings support the use of CBE as an accessible and effective intervention to promote cognitive health in elderly people.